Identıfıcatıon of KRAS Mutatıons in Colorectal Carcınoma Patıents at Dr. M. Djamıl Hospıtal, West Sumatra-Indonesıa - Rita Maliza; Hevi Horiza; Sumaryati Syukur; Allimuddin Tofrizal; Bramadi Arya (Medical Laboratory Technology Journal, 2023)
Kirsten rat sarcoma viral oncogene (KRAS) gene mutations lead to abnormal activation of the RAS signalling pathway and have been associated with poor prognosis and resistance to some therapeutics. This study aimed to identify mutation characteristics of the KRAS genes codon 12 and 13 in colorectal cancer patients in West Sumatra. KRAS mutations were analyzed in 20 DNA of colorectal cancer patients' tissue samples by using polymerase chain reaction (PCR) with specific primer and direct sequencing analysis. Our findings showed five samples (25%) with mutated KRAS at codons 12 and 13 (including three samples with GGT→GAT, one sample with GGT→GTT in codon 12, and one sample with GGC→GAC in codon 13). In conclusion, we found two variations of amino acid changes at codon 12 (G12D and G12V) and one at codon 13 (G13D). More research with many samples is required to obtain conclusive data on the relationship between these gene mutations and colorectal cancer response to therapy and prognosis.